A Systematic Review of Immersive Social Media Activities and Risk Factors for Sexual Boundary Violations among Adolescents - FS, Arsad; MIA, Abdul Khani; F, Daud (IIUM Medical Journal Malaysia, 2021)
Social media is appealing to the general public, especially the teenagers. This has brought about changes as the role of social media has penetrated our daily activities which directly affects the adolescence. This review looked at the usage of social media amongst adolescents and its impact on their sexual behaviour. Four databases were used in the literature search ie Web of Science, PubMed, EBSCOhost, and Ovid Medline. The search terms used revolved around social media, adolescent and social behaviour. Only English literature published from 2015 to 2020 were included. A total of 244 potentially relevant articles were identified in the initial search. 16 were excluded due to duplicates. A further 199 articles were excluded due to irrelevant population, intervention or outcome. Only 29 articles were suitable for narrative synthesis. The selected articles were analysed for risk factors and impact on the usage of social media on sexual behaviour. Sexual abuse, same-sex sexual activity, pornography, multiple online sexual partner, and sexual dissatisfaction were found to be negative impact. Positive impact included understanding of sexual role and consequences, safe sex practices and improved psychological well-being. This systematic review proved social media usage amongst adolescents have great impact on their sexual behaviour. Sexting was the main social media online sexual activity amongst adolescents which brings about negative sexual behaviours. This must be curb from earlier on which demands parental supervision in monitoring adolescence online activities.